Barriers to water markets in China's Heihe river basin - Zhang, Junlian (EEPSEA research report ; no.2005-RR8, 2005)
This study assesses the water use rights (WUR) system in Zhangye City, Gansu Province, Northwest China. The research was carried out to see how well the system performs, in terms of its impact on water conservation and redistribution, and to see what barriers stand in the way of its successful implementation. Under the WUR system, every water gets a water quota fixed by the government. WUR's can be sold, temporarily or permanently. The system was set up because Zhangye City is severely short of water. It is located in one of the driest area in the world and is mainly watered by the Heihe River. Almost all the water from the Heihe is currently extracted for irrigation and this has caused widespread desertification. The study finds that the WUR system is encountering significant problems. Farmers ignore their groundwater quotas and this is causing the region's aquifer to empty. The study also finds that water quota trades are still few and far between. There are many reasons for this failure, but a key issue is the financial insecurity of the region's farmers. There are also problems with the system itself, which encourages a "use it or lose it" attitude toward consumption. The study concludes that water use quotas and trading in China must go hand in hand with social and administrative improvements if it is to succeed.